2019
DOI: 10.1200/jco.2019.37.15_suppl.8524
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant nivolumab in resectable non-small cell lung cancer: Extended follow-up and molecular markers of response.

Abstract: 8524 Background: Improved therapy is needed for patients (pts) with early-stage non-small cell lung cancer (NSCLC), as the majority relapse after curative resection. Our group reported the first trial of neoadjuvant PD-1 blockade in resectable NSCLC, finding therapy to be safe and feasible. Here we report extended clinical follow-up and long-term molecular response data from this trial. Methods: IV nivolumab 3 mg/kg was given every 2 weeks for 2 doses prior to surgery in 20 pts with resectable NSCLC at Johns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The 24m RFS rate was 69% (95% CI: 51–93). 3 In terms of safety, this study showed treatment-related adverse reactions were 23%, only 1 case exceeded grade 3.…”
Section: Discussionmentioning
confidence: 64%
“…The 24m RFS rate was 69% (95% CI: 51–93). 3 In terms of safety, this study showed treatment-related adverse reactions were 23%, only 1 case exceeded grade 3.…”
Section: Discussionmentioning
confidence: 64%
“…Correlative analyses from NADIM trial are not currently available but, in the small cohort reported with atezolizumab plus Cht, MPR occurred regardless of PD-L1 TPS. Interestingly, molecular response data on neoadjuvant nivolumab suggests that ctDNA and peripheral T-cell expansion could be used as potential biomarkers for response and surveillance (45).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PD-1 blockade promoted systemic expansion of T-cell clones which shared similar T-cell repertoire with T-cells found in tissue, potentially eliminating microscopic metastatic disease. In the updated analysis with a follow up of 30 months, median RFS has not been reached and the 24 months RFS rate was 69% (95% CI: 51-93%) (45). The presence of circulating DNA (ctDNA) at diagnosis and MPR was not associated with RFS.…”
Section: Ici Monotherapymentioning
confidence: 97%
“…ctDNA appears to be present in 50–95% of stage I to III patients ( 32 , 33 ), suggesting that changes in ctDNA before and after neoadjuvant immunotherapy may be another more broadly applicable biomarker. The clearance of ctDNA and the expansion of tumor-specific T cells in peripheral blood may early monitor the treatment response and recurrence ( 34 ). However, whether ctDNA and tumor-specific T cells in peripheral blood are associated with MPR or even OS or DFS is not clear.…”
Section: Predictive Biomarkers Of Neoadjuvant Immunotherapymentioning
confidence: 99%